Exploring psychological counselors' perspectives on the characteristics and dynamics of online counseling - Buğa, Ahmet; Özdemir, Mehmet; Bozbayındır, Fatih (Frontiers in Psychology, 2026)
IntroductionThis study examines online psychological counseling with a focus on the therapeutic relationship and clients' self-disclosure behaviors, as perceived by experienced psychological counselors. With the increasing use of digital platforms in mental health services, understanding the opportunities and limitations of online counseling has become increasingly important.MethodsA qualitative phenomenological research design was employed. The study sample consisted of 14 psychological counselors who had experience conducting online counseling sessions. Data were collected through semi-structured interviews and analyzed using content analysis with the support of MAXQDA software.Results and conclusionThe findings indicate that online psychological counseling provides key benefits, especially greater accessibility and temporal-spatial flexibility. Nonetheless, technical difficulties (e.g., internet disruptions) and ethical issues related to confidentiality and trust remain important challenges. The strength of the therapeutic alliance was shaped by clients' personal characteristics and their adaptation to digital platforms. Online settings were perceived to facilitate self-disclosure among shy, privacy-sensitive clients or those who struggle with face-to-face interactions, while limited nonverbal cues were seen as restricting emotional communication and potentially weakening the therapeutic relationship. Self-disclosure was closely linked to perceived safety, relationship quality, and access to private, distraction-free environments. Participants also associated preferences for online counseling with demographic and personal factors such as age, socioeconomic status, and anxiety. In addition, online counseling supported counselors' professional development by enabling work with diverse clients, strengthening cultural competence, and improving time management. Overall, while online psychological counseling offers substantial opportunities, its effectiveness depends on individualized approaches, strong technological infrastructure, and clear ethical guidelines.